2016
DOI: 10.1016/j.cels.2016.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Deep Proteome Analysis Identifies Age-Related Processes in C. elegans

Abstract: SummaryEffective network analysis of protein data requires high-quality proteomic datasets. Here, we report a near doubling in coverage of the C. elegans adult proteome, identifying >11,000 proteins in total with ∼9,400 proteins reproducibly detected in three biological replicates. Using quantitative mass spectrometry, we identify proteins whose abundances vary with age, revealing a concerted downregulation of proteins involved in specific metabolic pathways and upregulation of cellular stress responses with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
113
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(129 citation statements)
references
References 58 publications
(83 reference statements)
15
113
0
Order By: Relevance
“…In addition, peroxisome import and protein expression decrease with age (Narayan et al, 2016). We therefore asked if peroxisomes have a role in drp-1;fzo-1 longevity.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, peroxisome import and protein expression decrease with age (Narayan et al, 2016). We therefore asked if peroxisomes have a role in drp-1;fzo-1 longevity.…”
Section: Resultsmentioning
confidence: 99%
“…To determine if peroxisomal function is required for drp-1;fzo-1 longevity we performed RNAi of prx-5 (ortholog of mammalian peroxisome biogenesis factor 5 (PEX5)). PRX-5/PEX5 is involved in the import of peroxisomal matrix enzymes (Narayan et al, 2016). Consistent with this and as previously reported (Narayan et al, 2016), prx-5 RNAi blocks import into peroxisomes, resulting in the mRFP-PTS1 fluorescence signal appearing diffuse, compared to punctate signal characteristic of peroxisomes in the control (Figure S5).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Surprisingly, the number of peroxisomes is increased in older cells, suggesting accumulation of the defective organelles with aging [24]. Recently, a quantitative mass-spectrometry-based study in Caenorhadbditis elegans identified ~30 peroxisomal proteins whose abundance decreased with aging [32]. One such protein identified was Pex5, an import receptor for peroxisomal matrix proteins containing a conserved C-terminal tripeptide called peroxisomal targeting sequence 1 [33,34].…”
Section: Relationship Between Peroxisomal Dysfunction and Agingmentioning
confidence: 99%